2016
DOI: 10.1016/j.rbmo.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CAG repeat length in the androgen receptor gene on male infertility – a meta-analysis

Abstract: CAG repeats are polymorphic nucleotide repeats present in the androgen receptor gene. Many studies have estimated the association between CAG repeat length and male infertility, but the conclusions are controversial. Previous meta-analyses have come to different conclusions; however, new studies have been published. An updated meta-analysis was conducted. PubMed, CBM, CNKI and Web of Science databases were systematically searched for studies published from 1 January 2000 to 1 October 2015. Case-control studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 64 publications
0
23
1
1
Order By: Relevance
“…Seminal clinical findings linked abnormally expanded CAG tract (>40 repeats) with reduced fertility and low sperm counts (La Spada et al, 1991). The association was further supported by the most recent meta-analysis including 40 studies (3858 cases and 3161 controls) published from 2000 to 2015 (Xiao et al, 2016). The association was further supported by the most recent meta-analysis including 40 studies (3858 cases and 3161 controls) published from 2000 to 2015 (Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Seminal clinical findings linked abnormally expanded CAG tract (>40 repeats) with reduced fertility and low sperm counts (La Spada et al, 1991). The association was further supported by the most recent meta-analysis including 40 studies (3858 cases and 3161 controls) published from 2000 to 2015 (Xiao et al, 2016). The association was further supported by the most recent meta-analysis including 40 studies (3858 cases and 3161 controls) published from 2000 to 2015 (Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 73%
“…Meta-analysis across~4000 fertile and infertile men of European origin has reported that the carriers of a prevalent allele with 22 CAG repeats have a lower risk for developing infertility compared to the men with longer and shorter repeats (Nenonen et al, 2011). The association was further supported by the most recent meta-analysis including 40 studies (3858 cases and 3161 controls) published from 2000 to 2015 (Xiao et al, 2016). Regarding the AR GGN-repeat tract, in vitro studies have shown that the most common variant (GGN n = 23) exhibits the highest transactivating capacity when compared with shorter or longer GGN stretches (Lundin et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…(MaxMean)2+(MinMean)24 Differences in recurrence rate and complication rate between the FG and suture groups were evaluated by OR with 95% CI, and SMD with 95% CI were used to estimate the difference in surgical duration between groups. We used the I 2 -statistic to calculate heterogeneity among the studies [48], I 2 > 50% implies significant heterogeneity resulting in the use of a random-effects model, otherwise a fixed-effects model was selected [24]. Due to the significant heterogeneity caused by a combination of different complications in the meta-analysis, we chosen a random-effects model to investigate complication rate.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the extent to which differences in the study region, patients and inconsistencies in case and control inclusion criteria between studies explain the conflicting outcomes is unknown. Therefore, meta-analysis provides a useful tool for the measurement of heterogeneity [24]. In fact, two published meta-analyses compared the efficacy of FG versus sutures in pterygium surgery in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The association between the AR-CAG repeat and male infertility has been intensively studied, but effects seem to be small and are still debated. Longer CAG repeat lengths may be a risk factor for male infertility, although population studies with variation detection in healthy controls argue against a strong association with unexplained male infertility, as concluded from large meta-analyses (Davis-Dao et al 2007;Xiao et al 2016). The transactivation domain of the AR comprises a further polyglycine tract (10-30 in length) encoded by a repeat consisting of GGN trinucleotides.…”
Section: Armentioning
confidence: 99%